2020
DOI: 10.1152/ajpheart.00484.2019
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxytocin and vasopressin in the pathophysiology of heart failure in pregnancy and in fetal and neonatal life

Abstract: Pregnancy and early life create specific psychosomatic challenges for the mother and child, such as changes in hemodynamics, resetting of the water-electrolyte balance, hypoxia, pain, and stress, that all play an important role in the regulation of the release of oxytocin and vasopressin. Both of these hormones regulate the water-electrolyte balance and cardiovascular functions, maturation of the cardiovascular system, and cardiovascular responses to stress. These aspects may be of particular importance in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 201 publications
(258 reference statements)
0
14
0
Order By: Relevance
“…The increase in duration of gestation could also be influenced by uterine sensitivity to oxytocin. In women with PE, oxytocin receptor expression is reduced and sensitivity to oxytocin is decreased in the uteroplacental unit (50,51). Akahoshi et al ( 52) also showed that the contractile response to oxytocin is reduced in mice with PE-like features.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in duration of gestation could also be influenced by uterine sensitivity to oxytocin. In women with PE, oxytocin receptor expression is reduced and sensitivity to oxytocin is decreased in the uteroplacental unit (50,51). Akahoshi et al ( 52) also showed that the contractile response to oxytocin is reduced in mice with PE-like features.…”
Section: Discussionmentioning
confidence: 99%
“…As recently discussed, the anti-inflammatory effects of OT have been supported under local and systemic levels (Buemann and Uvnäs-Moberg, 2020). There are recent reviews documenting that OT alleviates these immunoinflammatory abnormalities (Li et al, 2016;Bordt et al, 2019) with three referring to the actions of OT in the cardiovascular system (Reiss et al, 2019;Wang et al, 2019;Szczepanska-Sadowska et al, 2020). We have observed that following MI, rats preconditioned with OT displayed improvement of cardiac contractile function.…”
Section: Oxytocin and Inflammationmentioning
confidence: 92%
“…Secondly, NO, a key regulator of cardiac and vascular function, is involved in numerous actions in the heart and vascular beds by OT (Gutkowska et al, 2014). A number of social and reproductive behaviors such as breastfeeding, cutaneous contact between a mother and her infant, and sexual activity either alone with or others are linked to OT sensory stimulation (Buemann and Uvnäs-Moberg, 2020;Szczepanska-Sadowska et al, 2020). In addition, OT release is associated with reduced anxiety, depression, pain, inflammation, a reduction in the risk of cardiovascular disease and diabetes (Uvnäs-Moberg et al, 2014).…”
Section: Oxytocin In Cardiovascular Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was not based upon a direct measurement, as in humans, the short half-life of AVP makes the equimolarly released co-peptin a better biomarker. Similarly, in rats, AVP synthesis already starts during the prenatal life [42], and receptor expression and distribution patterns gradually change during the first period of life [43]. Accordingly, V1a receptor mRNA and ligand-binding capacity can be detected in rat fetus.…”
Section: Early Life Stress and Vasopressin: Possibility For Epigenetic Programmingmentioning
confidence: 97%